سلطة الإدارة في تعديل عقد الأشغال العامة أثناء مرحلة التنفيذ - العطراوي, كمال (جامعة الوادي University of Eloued, 2018)
الإدارة أثناء قيامها بإبرام العقود بمختلف أنواعها؛ عقد النقل، عقد الأشغال العامة، عقد التوريد، عقد الامتياز... وبهدف سهرها على سير المرافق العامة بانتظامـ- تلبية لاحتياجات المرتفقين - تتمتع بسلطات و امتيازات غير مألوفة في عقود القانون الخاص في مواجهة المتعاقد معها. من بين هذه السلطات و الامتيازات حق تعديل الإدارة للعقد الإداري دون أخذ رأي المتعاقد معها، مما قد يجعلها تتعسف في هذا الحق، الأمر الذي يحتم وجود رقابة قضائية على ممارستها لهذا الحق، تضمن التوازن بين سلطات الإدارة من أجل السير الحسن للمرافق العامة، وبين ما يصبو إليه المتعاقد وهو تحقيق الربح Abstract: Administration while making contracts of various kinds such as: contract of carriage, public works contract, supply contract, privilege contract … and in order to keep the regular function of public facilities - to meet the needs of beneficiaries-, it benefits of unusual powers and privileges in private law contracts in the face of the co-contractor. Among these powers and privileges, the right of administration to amend the administrative contract without taking the opinion of the co-contractor, which may make it abusive in this right, this case requires judicial control over the exercise of this right, that ensures the balance between the powers of the administration for the good conduct of public utilities and what the co-contractor aspires to is to make a profit.
Keywords: العقد الإداري، سلطة التعديل، سلطات الإدارة، القاضي الإداري